2021
DOI: 10.1177/13506501211023618
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of the static and dynamic characteristics of the precision hydrostatic spindle with mid-thrust bearing under different loads

Abstract: This paper investigates the static and dynamic characteristics of the precision hydrostatic spindle with a mid-thrust bearing under different working conditions. Firstly, the paper establishes the fluid governing equations of the coupled journal and thrust bearings based on orifice restrictors; and the dynamic and static Reynolds equations are solved using the perturbation and finite difference methods to obtain the steady and transient pressure distribution functions. Then the stiffness and damping characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Chen et al 12 proposed a dynamic modelling method that takes into account the pressure distribution in the bearing by integrating the flow equilibrium principle and finite-element theory, which establishes a direct correlation between the liquid film's characteristics and the dynamic performance of the spindle. Fang et al 13 investigate the static and dynamic characteristics of the precision hydrostatic spindle with a mid-thrust bearing under different working conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al 12 proposed a dynamic modelling method that takes into account the pressure distribution in the bearing by integrating the flow equilibrium principle and finite-element theory, which establishes a direct correlation between the liquid film's characteristics and the dynamic performance of the spindle. Fang et al 13 investigate the static and dynamic characteristics of the precision hydrostatic spindle with a mid-thrust bearing under different working conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many researchers have studied the mechanical characteristics of machine spindle units using the experimental methods. Fang et al [3] tested static and dynamic characteristics of the precision hydrostatic spindle with a mid-thrust bearing under different working conditions, and then studied the variation patterns in performance indices such as stiffness, damping, quasi-static position, and stability of the spindle under different working conditions. Song et al [4] studied the dynamic frequency response functions (FRFs) of the spindle-bearing system and its time-domain response under different cutting forces by establishing a dynamic model of the spindle-bearing system.…”
Section: Introductionmentioning
confidence: 99%
“…Chenggang Fang et al investigated how the hydrostatic bearing spindle offset affected the bearing's static and dynamic properties, and found that the spindle offset has little effect on the oil film thickness. With the increase of the cutting force, the force stiffness coefficient and moment stiffness coefficient are caused by the tilting motion of the spindle change significantly, but the z-axis direction's stiffness changes little [8].…”
mentioning
confidence: 99%